Testicular Tumors: A Contemporary Update on Morphologic, Immunohistochemical and Molecular Features. (12th July 2021) - Al-Obaidy, Khaleel I.; Idrees, Muhammad T.
Abstract : Testicular tumors are incredibly diverse and one of the most challenging areas in surgical pathology. Because of the rarity and overlapping features with numerous entities occurring in the testis and paratestis, these tumors pose a diagnostic challenge even to the most experienced general pathologists. In 2016, the latest "World Health Organization (WHO) classification of testicular tumors" was released, which incorporated several updates to the previous 2004 classification system. These updates involved several entities, including germ cell tumors, sex cord-stromal tumors, tumors containing both germ cells and sex-cord stromal cells, a miscellaneous group of testicular tumors and paratesticular tumors. In addition, significant changes were also introduced in the 2018 AJCC TNM staging (8th edition) regarding testicular tumors. The germ cell tumors are divided into 2 major groups; tumors derived from germ cell neoplasia in situ (GCNIS) and those unrelated to GCNIS. The GCNIS associated tumors include seminomatous and nonseminomatous germ cell tumors, which constitute a heterogeneous group of tumors. Non–GCNIS-associated tumors include prepubertal-type teratoma, prepubertal yolk sac tumor, mixed prepubertal-type teratoma and yolk sac tumor and spermatocytic seminoma. In the sex cord-stromal category, the tumors are classified based on their cells of origin. Most are Leydig cell tumors and Sertoli cell tumors; however, several mixed and diverse entities based on cell types are included in this group. Gonadoblastoma is the only tumor in the mixed germ cell and sex cord-stromal tumor category. Because of recent advances in molecular techniques, abundant new genetic information has emerged which helped classify the tumors based on the molecular alterations and provided insights into the tumor pathogenesis. This review focused on the updates related to testicular germ cell tumors and sex cord-stromal tumors and described the morphologic, immunohistochemical and molecular characteristics with an aim to provide a practical diagnostic approach and an update on relevant recent molecular advances.